Theory of Learning, Methods Development, and Practice of Basic Concept Dental Care Associated with Students' Academic Achievement - Eka Anggreni; Pudentiana Rr R. E.; Nita Noviani; Dwi Priharti; Siti Nurbayani Tauchid (GoAcademica Research & Publishing, 2022)
This study aims to develop methods and teaching materials on learning theories and practices of the Basic Concepts of Dental and Oral Care Services. The influence of learning interventions using textbooks and practical guidebooks impacts the achievement of theoretical value and the value of students’ practice in the clinic of Dental Nursing Department on Lebak Bulus III road number 1, South of Jakarta. This research design is quasi-experimental with a pre-test research design - post-test control group design. The sample in the research design consisted of two groups: the experimental group and the control group of 76 people. A pre-test is done to determine the initial state of the control and experiment group. The treatment effect was analyzed by statistical test, and if there was a significant difference between the experimental group and control, then the treatment group gave a significant influence. The result of the t-test is obtained p-value = 0,000 whose value is smaller than the error level α = 0.05 or with 95% significance then P <α, indicating a significant difference between the ability before compared after it. The basic concept and practice dental care guide has a very influential appeal that proves able to increase/motivate college students to recognize the concept, to sharpen the various domains that must be achieved to reach the target of competency, competency care process, and competency for the quality of service to the patient.